ENVIRONMENTAL-INDUCED MIGRATION AND LIVELIHOOD VULNERABILITY IN PATIGI LGA, KWARA-NORTH SENATORIAL DISTRICT, NIGERIA - Awotayo Gbenga Paul (Malaysian Journal of Tropical Geography (MJTG), 2023)
Migration and livelihood are interwoven so that both can be perceived as products of the environment. This paper provides an in-depth analysis of the global occurrence of forced migration as a result of environmental stress, which is a global challenge. However, approaches adopted in confronting it vary globally, and the present study contributes to global knowledge from a rare perspective. The approach solution to environmental stress holistically, particularly with the advocacy for community members’ participation at every stage of solution building, which was downplayed in the past in solving disaster-prone area challenges. It neglects the adoption of edge-cutting methods, such as the blue economy approach, that the old order did not have. The paper assessed the prevalence and occurrence of environmentally induced disasters in Patigi’s environs as well as their impact on livelihood vulnerability as a case study. The data for this study were obtained from a structured questionnaire, focus group discussions (FGD), and in-depth interviews. Purposive sampling was used by the National Emergency Management Agency to select five communities considered disaster-prone areas. These communities are Edochigi, Gudugi, Mawogi, Sokingi, and Gakpan. A total of 125 copies of structured questionnaires were administered using a disproportionate random sampling technique. Twenty-five disaster victims were selected from each community. The result showed that floods accounted for 72% of the prevalence of environmental disasters in the study area. Findings also revealed that 75.2% of the respondents are mostly farmers in rice cultivation. The correlation analysis shows that flooding greatly impacts farming, with a correlation of 0.615, especially during the rainy season. The study concluded that environment-related disasters had led to displacement and negatively impacted inhabitant livelihoods. The study recommended the need for community members’ involvement in the problem-solving process and the need to adopt the blue economy concept to minimize the adverse effects of disasters.